Some Whites are Whiter than others: the Whitefella Skin Politics of Xavier Herbert and Cecil Cook (Journal of the Association for the Study of Australian Literature, 2007)
Some Whites are Whiter than others: the Whitefella Skin Politics of Xavier Herbert and Cecil Cook